2018
DOI: 10.1016/j.ijppaw.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics and species-level systematics of Baylisascaris

Abstract: Nucleotide sequences representing nine genes and five presumptive genetic loci were used to infer phylogenetic relationships among seven Baylisascaris species, including one species with no previously available molecular data. These genes were used to test the species status of B. procyonis and B. columnaris using a coalescent approach. Phylogenetic analysis based on combined analysis of sequence data strongly supported monophyly of the genus and separated the species into two main clades. Clade 1 included B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 63 publications
2
30
1
Order By: Relevance
“…Due to the high level of divergence in the Cox1 gene, it is appropriate to consider it for phylogenetic and taxonomic studies of genus Baylisascaris . The results of some studies confirmed that mitochondrial genes are suitable markers for phylogenetic relationships and evolutionary biological aspects within the genus Baylisascaris [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Due to the high level of divergence in the Cox1 gene, it is appropriate to consider it for phylogenetic and taxonomic studies of genus Baylisascaris . The results of some studies confirmed that mitochondrial genes are suitable markers for phylogenetic relationships and evolutionary biological aspects within the genus Baylisascaris [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 82%
“…DNA sequence-based methods have been widely applied over recent years for species identification, classification and evaluation of phylogenetic relationships among ascarid nematodes [ 24 , 25 ]. Morphological differences between Baylisascaris species are not so clear; therefore, utilization of the sequence data will be helpful in this aspect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nematode specimens collected, the majority were determined to be B. tasmaniensis based on morphological and molecular analysis. Molecular sequences obtained in this study (GenBank sequences MW063459-MW063468) were a 100% match to a specimen of B. tasmaniensis (GenBank sequence MH030603; Camp et al, 2018) and clustered with B. tasmaniensis with 100% branch support (fig. 1; table 3).…”
Section: Resultsmentioning
confidence: 68%